ASX small firm/microcap listings: the IPO 'Pop' and two decades of subsequent returns. (1st December 2021) - Gilbey, Kylie; Marsh, Terry; Purchase, Sharon
Abstract: We examined IPO discounts and average returns for all available ASX (de)/listed IPOs from 1999 to 2019. We found that the average 18.45 percent offering discount was close to that observed in the US, as were the discount time series behaviour and distribution. Furthermore, the average annualised return on a market‐weighted portfolio of the ASX small/microcap IPOs, from close‐of‐listing‐day price to delisting or 31 December 2019, is 18.62 percent compared to 2.28 percent for large‐caps. Small/microcap post‐listing return differentials were highest for listings filed in Western Australia, and for the metals and mining and software industries.